Myocardial function during ventilation with lower versus higher positive end-expiratory pressure in patients without ARDS - Algera, AG; Pierrakos, C; Botta, M; Zimatore, C; Pisani, L; Tuinman, P-R; Bos, LDJ; Lagrand, WK; Gama de Abreu, M; Pelosi, P; Serpa Neto, A; Schultz, MJ; et al. (MDPI, 2022)
The aim of this study was to investigate whether lower PEEP (positive end-expiratory pressure) had beneficial effects on myocardial function among intensive care unit (ICU) patients without acute respiratory distress syndrome (ARDS) compared to higher PEEP. In this pre-planned substudy of a randomized controlled trial (RELAx), comparing lower to higher PEEP, 44 patients underwent transthoracic echocardiography. The exclusion criteria were known poor left ventricular function and severe shock requiring high dosages of norepinephrine. To create contrast, we also excluded patients who received PEEP between 2 cmH2O and 7 cmH2O in the two randomization arms of the study. The primary outcome was the right ventricular myocardial performance index (MPI), a measure of systolic and diastolic function. The secondary outcomes included systolic and diastolic function parameters. A total of 20 patients were ventilated with lower PEEP (mean ± SD, 0 ± 1 cmH2O), and 24 patients, with higher PEEP (8 ± 1 cmH2O) (mean difference, −8 cmH2O; 95% CI: −8.1 to −7.9 cmH2O; p = 0.01). The tidal volume size was low in both groups (median (IQR), 7.2 (6.3 to 8.1) versus 7.0 (5.3 to 9.1) ml/kg PBW; p = 0.97). The median right ventricular MPI was 0.32 (IQR, 0.26 to 0.39) in the lower-PEEP group versus 0.38 (0.32 to 0.41) in the higher-PEEP group; the median difference was –0.03; 95% CI: −0.11 to 0.03; p = 0.33. The other systolic and diastolic parameters were similar. In patients without ARDS ventilated with a low tidal volume, a lower PEEP had no beneficial effects on the right ventricular MPI.